The Role of Knowledge Management in Organization: A Survey of Banking and Insurance Companies in Central Java - Kusumadmo, E. (Journal of Human Capital, 2008)
The knowledge management is a major strategic imperative that supports financial organizations in a competitive environment. The importance of know/edge management is reflected in the fact that most of the managers saw their organizations as know/edge-based organizations that recognized the importance of knowledge, knowledge acquisition, knowledge dissemination and responsiveness to knowledge. Although various processes have been linked to knowledge management, it is clear that financial organizations realize that these processes must be supported by organizational culture and ICT usage. The first objective is to examine the causal relationship between internal organizational variables and knowledge management in the banking and insurance companies. The second objective is to determine the causal relationship between knowledge managementand competitive intensity in centrallavanese banking and insurance industry. The third objective of this study is to examine the conceptual models of knowledge management by testing the goodness of fit of the mode/s. This study surveyed the financial industrial environment by choosing the banking and insurance companies in three major cities in Centra/lava andlogjakarta Special Provnce as the research population (total sample, N-201). The research subjects were the branch managers ofthe bankingandinsurance companies who were considered to have a sound understanding of knowledge management in their respective companies Result found that knowledge management process shapedandsharedby the organization andderived from behaviors determining practices within the organization.Keywords : Knowledge Management, Organization Culture, /CT Usage, Business performance